2017
DOI: 10.1308/rcsann.2016.0225
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Ki-67 indices from biopsy and resection specimens of neuroendocrine tumours

Abstract: INTRODUCTION Neuroendocrine tumours (NETs) are a heterogeneous group of tumours with a highly variable presentation and prognosis. Management decisions are complex. Ki-67 levels in tissue samples are a key indicator used to grade tumours and guide treatment. This study assessed whether the Ki-67 index and tumour grade generated from tissue samples correlated with that assessed in resection specimens. METHODS This was a retrospective cohort analysis of all patients who had both a tissue sample and a resection s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…A recent standardization of Ki-67 LI on biopsy samples and the corresponding surgical specimens of Lu-NETs have demonstrated that results were quite superimposable with minimal deviation, even among different observers, provided that precise methodology rules were a priori established and used in either type of material (30). In keeping with other comparative studies (33,125), it was important to start identifying hot spot regions in either type of material in order to obtain overlapping results when counting 2,000 cells, 2-mm 2spanning areas or the entire biopsy fragment(s) (30). In this way, it was possible to attribute to unpredictable sampling, tissue sizing, intra-tumor heterogeneous distribution of Ki-67 antigen and inter-observer discordance when Ki-67 LI were discrepant between biopsies and the corresponding resection specimens (30).…”
Section: Identifying the Clinical Aggressiveness Of Neuroendocrine Tumentioning
confidence: 73%
See 2 more Smart Citations
“…A recent standardization of Ki-67 LI on biopsy samples and the corresponding surgical specimens of Lu-NETs have demonstrated that results were quite superimposable with minimal deviation, even among different observers, provided that precise methodology rules were a priori established and used in either type of material (30). In keeping with other comparative studies (33,125), it was important to start identifying hot spot regions in either type of material in order to obtain overlapping results when counting 2,000 cells, 2-mm 2spanning areas or the entire biopsy fragment(s) (30). In this way, it was possible to attribute to unpredictable sampling, tissue sizing, intra-tumor heterogeneous distribution of Ki-67 antigen and inter-observer discordance when Ki-67 LI were discrepant between biopsies and the corresponding resection specimens (30).…”
Section: Identifying the Clinical Aggressiveness Of Neuroendocrine Tumentioning
confidence: 73%
“…Another conundrum is the intra-tumor heterogeneous distribution of Ki-67 antigen likely due to the unpredictable occurrence of differentially regulated tumor cell subsets in tumors (115,120), but the consistent assessment of labeling indexes in hot spot regions will lead to more reproducible results (115). This biological phenomenon becomes particularly challenging on biopsy/cytology specimens in comparison with resection specimens (30,33,125) because of unpredictable sampling issues (the so-called tip-of-theiceberg effect or the part of the whole). Therefore, the reproducibility and clinical usefulness of Ki-67 LI in Lu-NETs have been seriously argued, with alleged superiority of mitotic count, which has remained the only proliferation criterion in tumor classifications over time (1,126,127), with no current diagnostic role for Ki-67 (1).…”
Section: Identifying the Clinical Aggressiveness Of Neuroendocrine Tumentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of correlation between Ki-67 and TGR 0 in this analysis was surprising. However, known difficulties in assessment of the Ki-67 index (intra- and intertumoral staining heterogeneity and counting methods, for example) may, in part, account for this [24, 25]. Ki-67 was not identified as a potentially important prognostic factor for PFS from the exploratory multivariate analysis, despite the known importance of Ki-67 as a prognostic marker in NETs [26].…”
Section: Discussionmentioning
confidence: 99%
“…Good correlation between grading from cytology and resection specimens using the Ki‐67 index has been demonstrated by various studies . Yet the use of the Ki‐67 index in small specimens still has the tendency to underestimate the histological grade . The underestimation is attributed to tumour heterogeneity .…”
Section: Introductionmentioning
confidence: 99%